ALIH FUNGSI (KONVERSI) PENGGUNAAN TANAH NEGARA DI KOTA MALANG - Tri Susilaningsih; Eduardus Marius Bo (Jurnal Cakrawala Hukum, 2017)
Function converse of land that was state land located at APP Tanjung and Veteran, outer stadium, TamanWilis and Rampal court was done based on regional regulation No. 7 year 2001 about RTRW which thearticles did not firmly show the requirement and the procedure of implementation. The function converse ofthis land caused the change of ecology, ecosystem, social cultureand even the social economic imbalance. RTHwhich had experienced the function converse was MATOS, Taman Wilisand MOG. While APP Tanjung,whichthe implementation of the function converse had not happened yet, had a sad view because there was still theremnant of building clearance of SPMA spreading on it although the function of RTH still existed. Rampalcourt which firstly would experience function converse was cancelled because it was maintained by kodamBrawijaya. This court gave more interesting view and freshened even it became RTH to make people healthy.RTH,which the function had been conversed,disappointed people and disordered city management which hadalready been suitable with area mapping. Function converse in Malang city had not been based on firm andclear regional regulation and it had not got the agreement from people, colleges or other governmental instanceslocated in the area around the function converse.